Pemanfaatan Media Baru Event via Live Streaming selama Pandemi Covid-19 - Tasya; Winduwati, Septia (Koneksi, 2022)
The emergence of the COVID-19 pandemic in Indonesia at the beginning of 2020 had many negative impacts in various sectors, one of which was to event organizers. On the other hand, with the advancement of modern technology in the digital field, new media have emerged that can support the planned and planned events using new media, namely live streaming. The theory used in this research is communication theory, computer mediated communication (CMC), determinism of communication technology. This research focuses on the experience gained for clients and event organizers with the existence of new media in the field of live streaming events. This study uses a qualitative research case study approach with data collection methods through interviews, and documentation. The results of this study indicate that live streaming events are a new medium in the event sector that provides experience, especially for event service users who can still hold events with new innovations, namely live streaming events that can help run the events that are being held. New media in the form of live streaming is enough to help individual activities or the business sector that offers services, in this case in the form of online events. The author also hopes that live streaming events as a new media can help the community in meeting their needs, especially in the event sector. Munculnya pandemi covid – 19 di Indonesia pada awal tahun 2020 memberikan dampak buruk di berbagai sektor, salah satunya penyelenggara event. Di sisi lain dengan kemajuan teknologi digital maka muncul media baru yang dapat menunjang jalannya acara dengan menggunakan media baru yaitu  live streaming. Teori yang digunakan dalam penelitian ini adalah teori komunikasi, computer mediated communication (CMC), determinisme teknologi komunikasi. Penelitian ini berfokus pada pengalaman yang didapatkan bagi klien maupun penyelenggara acara dengan adanya media baru dalam bidang event live streaming. Penelitian ini menggunakan penilitian kualitatif pendekatan studi kasus dengan metode pengumpulan data melalui wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa event live streaming merupakan media baru yang memberikan pengalaman, khususnya kepada pengguna jasa event yang tetap bisa menyelenggarakan acara dengan inovasi baru yaitu dengan event live streaming yang bisa membantu jalannya kegiatan acara yang dilangsungkan. Media baru berupa live streaming cukup membantu kegiatan individu ataupun sektor usaha yang menawarkan jasa, dalam hal ini berupa event online. Penulis juga berharap event live streaming sebagai media baru dapat membantu masyarakat dalam memenuhi kebutuhannya khususnya dalam bidang acara.